2021
DOI: 10.1186/s12929-021-00732-8
|View full text |Cite
|
Sign up to set email alerts
|

Notch-ing up knowledge on molecular mechanisms of skin fibrosis: focus on the multifaceted Notch signalling pathway

Abstract: Fibrosis can be defined as an excessive and deregulated deposition of extracellular matrix proteins, causing loss of physiological architecture and dysfunction of different tissues and organs. In the skin, fibrosis represents the hallmark of several acquired (e.g. systemic sclerosis and hypertrophic scars) and inherited (i.e. dystrophic epidermolysis bullosa) diseases. A complex series of interactions among a variety of cellular types and a wide range of molecular players drive the fibrogenic process, often in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 204 publications
(100 reference statements)
0
19
0
Order By: Relevance
“…Activation of Notch also upregulated the expression of ECM genes during stretching, suggesting that Notch might have an important role in ECM homeostasis during mechanical stress. Previous studies have shown that ECM proteins can affect Notch Condorelli et al, 2021). However, to our knowledge, the role of Notch in regulating ECM production in VSMCs had not been explored yet.…”
Section: Discussionmentioning
confidence: 93%
“…Activation of Notch also upregulated the expression of ECM genes during stretching, suggesting that Notch might have an important role in ECM homeostasis during mechanical stress. Previous studies have shown that ECM proteins can affect Notch Condorelli et al, 2021). However, to our knowledge, the role of Notch in regulating ECM production in VSMCs had not been explored yet.…”
Section: Discussionmentioning
confidence: 93%
“…The Notch signaling cascade consists of membrane-bound ligands known as Delta-like (Dll1, Dll3, Dll4), Jagged1 and Jagged2, and Notch receptors (referred to as Notch1, Notch2, Notch3, Notch4) that can interact within the same cell (cis) or across cell boundaries (trans) [ 152 , 161 , 162 ]. The binding between Notch receptors and ligands results in γ-secretase-mediated Notch cleavage and consequent release of the active Notch intracellular domain (NICD) that, once translocated into the nucleus, aggregates with the CSL transcription factor complex and stimulates the transcription of Notch target genes [ 152 , 161 , 162 ]. Several studies demonstrated the activation of Notch signaling in SSc skin and fibroblasts, as well as in SSc mouse models [ 152 , 163 , 164 , 165 ], but only one investigated pharmacological inhibition of such pathway in this pathologic condition [ 165 ].…”
Section: Main Molecular Pathways Driving Myofibroblast Differentiation From Vascular Wall Residing Cells In Systemic Sclerosis and Relatementioning
confidence: 99%
“…The most prevalent SNPs were rs1800469 in TGFβ1 (41%) and rs3957356 in G STA1 (36%). TGFβ1 encodes a protein that acts on the inflammatory response pathways by repairing DNA lesions; however, it is not yet known whether SNPs can affect the function of this protein [59,60]. G STA1 is involved in the production of reactive oxygen species, and SNPs can promote increased radiosensitivity through indirect damage to the DNA of skin cells [61].…”
Section: Breast Cancer Patientsmentioning
confidence: 99%